Court Decision (In Constitutional Aspect) - Irham; Fauziah Roihana Siregar; Dimas Sunanta (ISNU Nine-Star Multidisciplinary Journal, 2024)
The birth of a court decision is the end result of a complex judicial process, reflecting the application of law and justice. This process begins from the filing of a lawsuit to the examination of evidence, with the judge as the party who plays a vital role in ensuring justice and objectivity. The background of this study is the need for a more efficient and flexible settlement mechanism in the Judicial Institutions in Indonesia. This study uses the Meta-Analysis Method, a method that synthesizes the results of various studies to determine the average impact of similar interventions across studies. Meta-analysis is a statistical analysis that combines the results of several scientific studies. Data were obtained through analysis of legal documents, court decisions, and interviews with legal practitioners and parties who understand court decisions. The results of the study show that the decision provides certainty and protection for the parties involved. Court costs and compensation mechanisms are also important aspects that affect the accessibility of justice.